Using Rich Lists to Study the Super-Rich and Top Wealth Inequality: Insights from Switzerland - Enea Baselgia; Isabel Z. Martínez (Center for Economic Studies and ifo Institute (CESifo), 2024)
We present a new data set we built based on Swiss rich lists going back to 1989. We show, among other things, that 60% of the super-rich are heirs—a fraction twice as large as in the US—and that wealth mobility at the very top has declined significantly. We find that top 0.01% wealth shares are higher than previous estimates based on wealth tax statistics suggest. At the same time, we argue that rich list data lead to overestimating wealth inequality. While rich lists are valuable to study the super-rich, we recommend to use reported wealth figures with caution.
Keywords: C81; D31; D64; J62; 330; super-rich; wealth inequality; inheritances; wealth mobility